If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4z + 4 = 9z + -28 Reorder the terms: 4 + 4z = 9z + -28 Reorder the terms: 4 + 4z = -28 + 9z Solving 4 + 4z = -28 + 9z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-9z' to each side of the equation. 4 + 4z + -9z = -28 + 9z + -9z Combine like terms: 4z + -9z = -5z 4 + -5z = -28 + 9z + -9z Combine like terms: 9z + -9z = 0 4 + -5z = -28 + 0 4 + -5z = -28 Add '-4' to each side of the equation. 4 + -4 + -5z = -28 + -4 Combine like terms: 4 + -4 = 0 0 + -5z = -28 + -4 -5z = -28 + -4 Combine like terms: -28 + -4 = -32 -5z = -32 Divide each side by '-5'. z = 6.4 Simplifying z = 6.4
| 7b-70-9b=0 | | 15x+5=26x-6 | | 12x=6x+3 | | -7+9h=8h | | -62=7x+8 | | 3w+7=4w+13 | | 5x/3=11 | | 2x+y-4(x+2y)=13-2(3y-x)+y | | 3y+8=8y-8 | | f(x)=x^4+5x^2+6 | | 4=7x+8 | | 1+1k=1+1k | | 2(x+y)-4(x+y)=8(x+2)-8(y-2) | | 9y^2+37y+9= | | 8x+5=3x+38 | | 6=-6x+3y | | 6=-6+3x | | (9+8n)+(-4-3n)+(3+6n)= | | C-u=n+t | | 3n+4=32-4n | | 6=6x+3y | | -20+(20d)=100 | | 5-4+7x+1=6x+9 | | 1/3=4/g | | 7x+16=2(8x+1)-4 | | A=3b-cx | | 14x+1=78 | | 1y+2y+3y=42 | | 24x=-23 | | 9b-6=6b | | 4z+5=5z-1 | | 3y=2z+8solvez |